2013
DOI: 10.1186/1471-2458-13-368
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of medium-term exposure to ambient nitrogen dioxide pollution and hospitalization for stroke

Abstract: BackgroundThere are several plausible mechanisms whereby either short or long term exposure to pollution can increase the risk of stroke. Over the last decade, several studies have reported associations between short-term (day-to-day) increases in ambient air pollution and stroke. The findings from a smaller number of studies that have looked at long-term exposure to air pollution and stroke have been mixed. Most of these epidemiological studies have assigned exposure to air pollution based on place of residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The potential differential effect of particulate matter from exhaust and non-exhaust sources is an areas which warrants further investigation. The lack of association observed between long-term exposure and risk all ischaemic or haemorrhagic stroke is in line with findings from previous studies (Johnson et al, 2013;Johnson et al, 2010;Maheswaran et al, 2012). Only one study of the long-term effects found a significant increased risk of haemorrhagic stroke associated with long-term exposure to N0 2 in Japan (Yorifuji et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The potential differential effect of particulate matter from exhaust and non-exhaust sources is an areas which warrants further investigation. The lack of association observed between long-term exposure and risk all ischaemic or haemorrhagic stroke is in line with findings from previous studies (Johnson et al, 2013;Johnson et al, 2010;Maheswaran et al, 2012). Only one study of the long-term effects found a significant increased risk of haemorrhagic stroke associated with long-term exposure to N0 2 in Japan (Yorifuji et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…concentrations averaged over months or years, usually measured at place of residence. Some studies found no associations with stroke risk (Johnson et al, 2013;Maheswaran et al, 2014;Maheswaran et al, 2012;Yorifuji et al, 2013). The European ESCAPE cohort study found a 5-μg/ m3 increase in annual PM 2.5 exposure associated with 19% increased risk of incident stroke, with similar findings for PM 10 (Stafoggia et al, 2014).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Most commonly reported pollutants included long-term exposure to PM 10 6, 10, 14, 15 , PM 2.5 10, 11, 16 and NO x 6, 17, 18 or NO 2 8, 14, 15, 19, 20 . Many of the cohort studies reported positive associations 8, 10, 11, 14, 21 whereas ecological studies 6, 15, 19 and case-control studies 17, 18, 21 showed mixed results. In a random-effects meta-analysis of 11 European cohorts 16 , long-term PM 2.5 was associated more strongly associated with stroke in subjects older than 60 years old, never-smokers and among subjects with exposure levels less than 25 µg/m 3 (current annual mean air quality standard in Europe).…”
Section: Long-term Air Pollution Exposurementioning
confidence: 99%
“…This reason suggests an environmental etiology for atherosclerosis [12]. At the same time, a Canadian study found a greater association between short-term exposure and the development of stroke [13].…”
Section: Introductionmentioning
confidence: 99%